Formulation and Antibacterial Activities of Chewable Lozenges of Celery (Apium graveolens L.) Leaf Ethanolic Extract against Dental Caries Causing Streptococcus mutans - Vella Lailli Damarwati; Rizka Wahyu Septiasih; Zaki Tiffani Lazuardian; Annisa Krisridwany (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Celery (Apium graveolens L.) is an herbal plant that has the chemical content flavonoid, saponin and tannin. The antibacterial activity of them have been investigated for many years. However, the antibacterial activity has not been evaluated in oral formulations. This study aims to formulate chewable lozenges celery leaf ethanolic extract, evaluate physical characterized and antibacterial activity of chewable lozenges. Celery leaf ethanolic extract is formulated into chewable lozenges using molded method with concentration of 20 g and 25 g. This formulation was characterized for organoleptic test, weigh uniformity, dissolution testing, thickness testing and pH determination. Antibacterial activity of chewable lozenges was carried out by diffusion method using Streptococcus mutans. From the chewable lozenges formula there are no significant physical differences between formulas and can be organoleptically acceptable. The results of the antibacterial activity test showed the value of inhibition zone diameters of Streptococcus mutans bacteria in F1, F2, F3, F4, F6 respectively 8,8 mm, 9 mm, 8,16 mm, 9,33 mm, 8 mm dan 9,13 mm. Formulation F4 shown better antibacterial activity as compared to its other formulations.